Improvement of messages delivery time on vehicular delay-tolerant networks - Soares, V.N.G.J. (2009)
Vehicular Delay-Tolerant Networks (VDTNs) are an application of the Delay-Tolerant Network (DTN) concept, where the movement of vehicles and their message relaying service is used to enable network connectivity under unreliable conditions. To address the problem of intermittent connectivity, long-term message storage is combined with routing schemes that replicate messages at transfer opportunities. However, these strategies can be inefficient in terms of network resource usage. Therefore, efficient scheduling and dropping policies are necessary to improve the overall network performance. This work presents a performance analysis, based on simulation, of the impact of different scheduling and dropping policies enforced on Epidemic and Spray and Wait routing schemes. This paper evaluates these policies from the perspective of their efficiency in reducing the message’s end-to-end delay. In our scenario, it is shown that when these policies are based on the message’s lifetime criteria, the message average delay decreases significantly and the overall message delivery probability also increases for both routing protocols. Further simulations show that these results outperform the MaxProp and PRoPHET routing protocols that have their own scheduling and dropping mechanisms.